2015
DOI: 10.1063/1.4907012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of oxygen adsorption on the NEXAFS and core-level XPS spectra of the C60 derivative PCBM

Abstract: A comparative theoretical study on core-hole excitation spectra of azafullerene and its derivatives J. Chem. Phys. 140, 124304 (2014) The influence of oxygen adsorption on the NEXAFS and core-level XPS spectra of the C 60 derivative PCBM Fullerenes have been a main focus of scientific research since their discovery due to the interesting possible applications in various fields like organic photovoltaics (OPVs). In particular, the derivative [6,6]-phenyl-C 60 -butyric acid methyl ester (PCBM) is currently one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
4
23
0
Order By: Relevance
“…The mechanism for the loss of conjugation due to the breaking of CQC bonds in the PC 70 BM cage is similar to what has been previously established for PC 60 BM, both theoretically by Brumboiu et al 48,54 and experimentally by Anselmo et al 25 The breaking of CQC bonds may also lead to the opening of the C 70 cage. 17 In contrast to the TQ1:PC 60 BM blend (Hansson et al 27 ), the presence of TQ1 decelerates the photo-oxidation of the PC 70 BM component in the TQ1:PC 70 BM blend.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The mechanism for the loss of conjugation due to the breaking of CQC bonds in the PC 70 BM cage is similar to what has been previously established for PC 60 BM, both theoretically by Brumboiu et al 48,54 and experimentally by Anselmo et al 25 The breaking of CQC bonds may also lead to the opening of the C 70 cage. 17 In contrast to the TQ1:PC 60 BM blend (Hansson et al 27 ), the presence of TQ1 decelerates the photo-oxidation of the PC 70 BM component in the TQ1:PC 70 BM blend.…”
Section: Discussionsupporting
confidence: 84%
“…47 The first peak has been assigned to the C1sp* transitions in the PC 70 BM molecule and the main contributions are likely to be from the sp 2 carbons of the fullerene cage, as is the case for PC 60 BM. 48 The peak intensity, i.e., the probability of transitions, can to some extent be related to the density of available final states for this transition, in other words the density of states (DoS) in the LUMO.…”
Section: Nexafs Of Pc 70 Bmmentioning
confidence: 99%
“…The two initial low intensity O(1s) peaks observed in the PC 61 BM become a single strong broad signal on aging, which suggests multiple similar chemical states may be present for oxygen. Unfortunately, it has been previously calculated that a wide range of O(1s) peak positions are possible depending on the location of the oxidation on the PC 61 BM molecule [50], with similarly complex results also previously noted for the oxidation of PC 71 BM [17]. This suggests that the simple two peak fitting of the O(1s) envelope used in Table 1 is a significant simplification of the true complex system once oxidation has occurred.…”
Section: Msupporting
confidence: 52%
“…Such reaction has been well investigated for fullerene molecules, with the formation of epoxides and carbonyls on the C 60 cage both identified as the photochemical degradation products. [ 9,10 ] The photooxidation of NFA molecules is relatively less understood, which requires further analysis. Taking ITIC for example, photooxidation reaction may occur at multiple sites of the molecular structure (Figure 10b), including the double bonds between the donor and acceptor units, on the thiophene or bithiophene outlying central building blocks and side chains.…”
Section: Toward Superior Stability Of Nfa‐based Oscsmentioning
confidence: 99%
“…In addition, some studies have shown that a number of degradation mechanisms of fullerene acceptor‐OSCs under various environmental conditions are related to the high sensitivity of fullerene acceptors to light and oxygen, as well as their tendency to form detrimental macroscopic aggregates under thermal stress. [ 9,10 ] Therefore, there has been a strong need for alternative electron acceptor materials to improve OSC performance (efficiency and stability) further and hence to exploit the commercialization potential of OSCs.…”
Section: Introductionmentioning
confidence: 99%